Who has to pay for measures in the field of water management? A proposal for applying the polluter pays principle - Grünebaum, Thomas (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
There is no doubt about the fact that the implementation of the European Water Framework Directive (WFD) and the pursuit of its goal of good ecological status will give rise to measures in different fields of water management. However, a conclusive and transparent method of financing these measures is still missing up to now. Measures in the water management sector are no mere end in themselves; instead, they serve specific ends directed at human activities or they serve general environment objectives. Following the integrative approach of the WFD on looking upon river basins as a whole and its requirement to observe the polluter pays principle, all different groups within a river basin should contribute to the costs according to their cost-bearer roles as polluters, stakeholders with vested interests or beneficiaries via relevant yardsticks. In order to quantify the financial expenditure of each cost bearer, a special algorithm was developed and tested in the river basin of a small tributary of the Ruhr River. It was proved to be generally practicable with regard to its handling and the comprehension of the results. Therefore, the application of a cost bearer system based on the polluter-pays principle and thus in correspondence with the WFD's requirements should appear possible in order to finance future measures